PERFORMANCE OF PROMISING HYBRID RICE IN TWO DIFFERENT ELEVATIONS OF IRRIGATED LOWLAND IN INDONESIA - Widyastuti, Yuni; Satoto, Satoto; Rumanti, I.A. (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2015)
The hybrid rice program has been established since early 1990âs at the Indonesia Center for Rice Research (ICRR). Twenty-four experimental hybrid rice varieties which have been developed were tested in lowland rice fields in Sukamandi (West Java) and Batang (Central Java) during the dry season and the rainy season of 2012. Randomized complete block design (RCBD) with three replications was used in each location. The results showed that grains yields were affected by locations, seasons, and genotypes. The genotypes x locations x seasons interaction effect was significant; therefore, the best hybrid was different for each location and season. A7/PK36 hybrid has the best performance in Batang during the dry season, while A7/PK40 and A7/PK32 are the best hybrids in the rainy season. In Sukamandi, nine hybrids were identified as better yielder than that of the check cultivar in the dry season, but not so in the rainy season. Using the correlation and path analysis, we found that the number of panicles per hill and the number of filled grains per panicle could be used as selection criteria for yield in hybrid rice.Â Keywords: agronomic performance, correlation, hybrid rice, lowlandÂ